(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
Currently, companies exist in a scenario where competitiveness is a limiting factor to survival. Many entrepreneurs are unable to effectively manage their enterprises due to not knowing the management techniques and tools, especially regarding financial aspects. The cash flow budget is a forecasting model capable of meeting the needs of financial management since cash management directly influences the payment capacity, liquidity, and results of companies. This study aims to address the relevance of cash flow, as a tool to assist in decision-making and improve companies’ financial resources and to present some methods to mitigate uncertainties in budget forecasts. The methodology used in this study was characterized as descriptive, by a bibliographic research, with a qualitative approach. The results of the bibliographic survey indicated three main methods used to reduce uncertainty in the preparation of the cash flow budget: sensitivity analysis, scenario analysis and Monte Carlo method. The Monte Carlo method appears in several studies as the most effective in mitigating the risks of forecasting, since it allows probabilistically analyzing several possible scenarios.